Miejsce pogan w rzeczywistości eschatologicznej apokalips żydowskich powstałych pomiędzy rokiem 70 a 132 po Chr - Miduch, Maria (Poznańskie Studia Teologiczne, 2014)
Jewish apocalyptic literature appeared in the period between the destruction of the Temple in Jerusalem and the outbreak of the Bar Kokhba Revolt and bears the marks of the difficult times of the Roman occupation, and the persecution which the chosen people suffered at this time. The theological ideas presented in the texts of the four apocalypses illustrate the diversity of Judaism of the period. The expectations of the authors of these texts regarding the future are so varied that one can identify five basic eschatological concepts which are described here as ‘nationalistic eschatology’, ‘traumatic eschatology’, ‘eschatology of hope’, ‘idyllic eschatology’, and ‘universal eschatology’. In these eschatological models different importance is attached to the pagan nations surrounding the people of Israel. The role which they play in eschatological visions is largely conditioned by the circumstances under which these particular texts were created. Keywords